Kształtowanie się opinii personelu więziennego wobec skazanych muzułmanów o odmiennych potrzebach kulturowych - Urbanek, Arkadiusz (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2018)
The article discusses the diagnosis of a part of organizational culture of Polish and Lithuanian system. Organizational culture includes here opinions expressed by the staff as well as rules shaping the way of reacting to the presence of Muslim prisoners and at the same time, persons declaring distinct cultural needs. Both penitentiary systems are similar due to limited experience in working with Muslim prisoners. Another common characteristic of the systems is the fact that European Union recommendations from the year 2012 concerning the shaping of cultural competencies of prison officers are applicable in both of them. The text aims at answering the following questions: What are the opinions of officers towards the Muslims who express the needs connected with their culture? Statistically, how often do the same opinions occur?
Keywords: Muslims; prison; organizational culture